Fertilização orgânica no desenvolvimento da leguminosa crotalária juncea (Crotalaria juncea L.) - Araújo, Wildjaime de Bergman Medeiros de (2008)
The objective of this work was to evaluate the performance of the Crotalaria juncea, under applications of different doses of cattle manure and of earthworm humus. An experiment was carried out in the period of August to October of 2007 in the greenhouse of the Plant Science Department of the Universidade Federal Rural do Semi-Árido (UFERSA), Mossoró-RN. A 2 x 5 factorial scheme with thee replications of two plants per plot in a completely randomized design was used. The treatments consisted of the combination of two sources of organic matter ( cattle manure and earthworm humus ) with five doses of these sources ( 0, 15, 45, 60 t ha-1 ) the doses of organics fertilizers were incorporated to the total soil volume and, soon after application of the treatments it was sowed five seeds per pot with Crotalaria juncea, leaving later two plants per pot. The evaluated traits were: plant height and stalk diameter, number of leaves per plant, shoot fresh and dry mass. Significant interaction between sources of organic matter and their doses was observed on plant height, stalk diameter and number leaves per plant. The highest plant height ( 173.50 cm) and stalk diameter (4,83 cm) were obtained with the dose application of 45 t ha-1 of cattle manure, being this value 24% higher as compared to that value in the same dose of earthworm humus. These was not significant the interaction between sources of organic matter and their doses on shoot fresh and dry mass. The Crotalaria juncea responded very well the input of the organic matter sources. The dose of organic matter to be recommended for fresh production of Crotalaria juncea is of 40 t ha-1 . the production of more vigorous plants was provided by the cattle manure